Rethinking immigration policy theory beyond ‘Western liberal democracies’ - Katharina Natter (Comparative Migration Studies, 2018)
Abstract How do political systems shape immigration policy-making? Explicitly or implicitly, comparative politics and migration policy theories suggest a ‘regime effect’ that links specific dynamics of immigration policy to liberal democracy. The literature’s dominant focus on so-called ‘Western liberal democracies’, however, has left the ‘regime effect’ largely untested and research on variations and similarities in immigration policymaking across political systems strikingly undertheorized. This paper challenges the theoretical usefulness of essentialist, dichotomous categories such as Western/non-Western or democratic/autocratic and calls for a more nuanced theorizing of immigration policy-making. It proposes a two-dimensional classification of immigration policy theories, distinguishing between ‘issue-specific’ theories that capture immigration policy processes regardless of the political system in place and ‘regime-specific’ theories whose insights are tied to the characteristics of a political system. The paper also advances the ‘illiberal paradox’ hypothesis to explain why illiberal, autocratic states may enact liberal immigration policies. This theoretical expansion beyond the ‘Western’ and ‘liberal’ bubble is illustrated by an analysis of immigration policy-making in 21st century Morocco and Tunisia. Showing how domestic and international institutions, interests, and ideas shape immigration policy-making in Morocco’s monarchy and Tunisia’s democratic transition, the paper investigates the broader role of political systems in immigration politics and herewith seeks to contribute to a more general and global theorization of immigration policies.